Enhancement the Performance of Asphalt Pavement Using Fly Ash Wastes in Saudi Arabia - Dahim, Mohammed; ., . (International Journal of Engineering and Technology, 2018)
Saudi Arabia is the largest Arab country and is one of the most prolific producers of oil and energy consumption. The Kingdom uses heavy oil and diesel to generate electricity and desalinate seawater. This produces large amounts of ash, a toxic substance that is disposed of by landfill and may cause many environmental problems and contribute to pollution of groundwater, which is one of the most important sources of drinking water. This paper presents the possibility of using fly ash by-product waste from electric power generation plants to improve the properties of asphalt mixtures. This study investigates the use of two types of fly ash namely; class C and class F was used as a filler in two types of bitumen and asphalt material known as AC 40/50 and AC 60/70. The rheological performance of asphalt with different percentages of fly ash filler ranging from 0% to 10% with an increment of 2% was tested. The rheological properties of both asphalts modified using both types of ash were determined. The rutting factors of the modified asphalt with fly ash content were calculated using the rheological properties. The result indicates that rutting resistance of asphalt could be improved by both types of fly ash which can be lead to reduces the costs of repairing and rehabilitation of asphalt pavement and reduce environmental impacts of a significant amount of toxic waste fly ash. Class F fly ash shows higher rutting factor than class C. Also AC 60/70 asphalt possess higher rutting factor than AC 40/50 asphalt at both low and high temperature.Â Â